The preparation and properties of a transparent coating based on organic silicone resins. Issue 1 (5th January 2015) - Cheng, Jia-Neng; Liu, Yan; Che, Hongwei; Yan, Guoping; Liu, Xinghai; Liu, Xiaojing; Wang, Xiaoyan; Bi, Bo
Abstract : Purpose: – The purpose of this investigation was to study a transparent coating based on organic silicone resins prepared by the hydrolysis and condensation of methyltriethoxysilane and tetraethoxysilane. Design/methodology/approach: – The coating film was characterized by IR, UV, thermal gravity analysis, scanning electron microscope and an automatic contact angle meter. Some properties of the coating film, such as adhesion, impact resistance and wear-resistance also were evaluated. Findings: – These uniform, clear and smooth coating films possessed the high transparent and light transmittance, high density, high hydrophobicity, good adhesion, hardness and anti-corrosion. Originality/value: – The coating may be considered as a protective film for the surfaces of the metals and plastics.